Identity and Distribution of Triglops metopias (Teleostei, Cottidae) in the Northwestern Pacific - Artem M. Prokofiev; Ilyas N. Mukhametov; Olga R. Emelianova; Svetlana Yu. Orlova; Alexei M. Orlov (Journal of Marine Science and Engineering)
The Alaskan (highbrow) sculpin, Triglops metopias, is a rare and poorly known species with a restricted distribution in the North Pacific. This species has been previously recorded only from off the Aleutian Islands and the Gulf of Alaska, while previous records from the western North Pacific have been controversial. The presence of T. metopias in the northwestern Pacific off the Kuril Islands is confirmed in the current study. Forty-one specimens were included in morphological and molecular analyses, including principal component analysis and DNA barcoding. The detailed morphological description of the Kuril Islands specimens is given. Molecular analysis inferred from the mitochondrial cytochrome b sequences showed no separation of this species from T. pingelii, although they can be distinguished by external morphology, including the use of the multivariate statistical approach. The geographical distribution of T. metopias in the North Pacific is discussed. This species is considered to be a recently diverged species with a disjunct distribution from the Kuril and the Aleutian Islands eastwards to the Gulf of Alaska. Despite its morphological similarity to T. pingelii, both species can be distinguished by a combination of meristic and morphometric characters, in particular, the wider interorbital space (10.4–22.4, mean 14.8 vs. 6.9–11.4, mean 9.2), shorter pectoral fins (18.7–24.9, mean 21.0 vs. 21.7–27.4, mean 24.1), and the on average more numerous oblique dermal folds (92 vs. 54).